Prevalence and Predictors of Obstructive Sleep Apnea in Patients with Chronic Obstructive Pulmonary Disease Undergoing Inpatient Pulmonary Rehabilitation. (4th May 2018) - Schreiber, Annia; Cemmi, Francesca; Ambrosino, Nicolino; Ceriana, Piero; Lastoria, Cinzia; Carlucci, Annalisa
Abstract: The aim of our study was to evaluate the prevalence and predictors of obstructive sleep apnea (OSA) in patients with chronic obstructive pulmonary disease (COPD) undergoing inpatient pulmonary rehabilitation programs (PRPs). A retrospective data review of consecutive stable patients with a known diagnosis of COPD, admitted for PRP between January 2007 and December 2013. Full overnight polysomnography (PSG) and Epworth Sleepiness Scale (ESS) were assessed in all patients. Out of 422 evaluated patients, 190 (45%) showed an Apnea Hypopnea Index (AHI) ≥ 15 events/hour and underwent OSA treatment. Patients with OSA were significantly younger and had a less severe airway obstruction as compared to patients without OSA. There were no significant differences in cardiac comorbidities nor in arterial blood gases. As expected, patients with OSA showed significantly more severe diurnal symptoms, as assessed by the ESS and higher body mass index (BMI). However, only 69 out of 190 patients with OSA (36.3%) showed an ESS >10, whereas 25% of them had BMI ≤25 and 41% of them had a BMI <30. In all, 68% of patients with OSA were discharged with continuous positive airway pressure (CPAP), 15% with Bilevel ventilation, and 17% without any ventilatory treatment. In conclusion, in the population studied, the combination of OSA and COPD was frequent. BMI and ESS values commonly considered cutoff values for the prediction of OSA in the general population may not be accurate in a subgroup of patients with COPD.